Studi Komparasi Konsep Tuhan dalam Mistisisme Jawa dan Advaita Vedanta Adi Śańkarācārya - Gede Agus Siswadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Mysticism gives a different nuance in defining the concept of God. Because this is related to the individual experience of those who reach the mystical consciousness, awareness of God in mysticism cannot be reached by reason or empirically but through the way of the senses in mind. This article attempts to explain the concept of God in Javanese mysticism and Advaita Vedanta Adi Śańkarācārya. The method used in this research is (library research). The results of this study are 1) the concept of God in Javanese mysticism (Sangkan Paraning Dumadi) and Advaita Vedanta (Brahman as the highest and absolute reality) is monistic theism, namely understanding God as one (transcendent monotheism). 2). In the view of Javanese mysticism, the universe is sourced from God and will return to God, while in Advaita Vedanta, apart from Brahman as an absolute reality, everything else, including nature, is an illusion of Maya. 3). To achieve God's consciousness, Javanese mysticism emphasizes doing Heneng, Hening, Henong, and Catur Lampah Laku, with the spiritual path to reach Manunggaling Kawula Gusti. Whereas in Advaita Vedanta, the union between Atman and Brahman can be achieved by removing the veils of Maya and avidya (ignorance).